2020
DOI: 10.1055/a-1221-4733
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Grape and Apple Juices against Cadmium Intoxication in the Kidney of Rats

Abstract: Background The objective of this study was to evaluate protective effect of grape and apple juices against toxicity induced by cadmium in the kidney of rats. Methods A total of 20 male-Wistar rats were distributed into four groups (n=5): Control group: animals received an intraperitoneal (i.p.) injection of 0.9% saline solution and after 15 days, 1 mL of water was administered for 15 days, vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 43 publications
0
3
0
2
Order By: Relevance
“…The main harm of cadmium to the human body is kidney damage. Nearly 50% of the cadmium is accumulated in the kidney, especially in the proximal convoluted tubule, leading to kidney damage and chronic kidney disease [5][6][7][8]. Previous studies revealed that up to 7% of the global population suffers from chronic kidney disease caused by cadmium [9].…”
Section: Introductionmentioning
confidence: 99%
“…The main harm of cadmium to the human body is kidney damage. Nearly 50% of the cadmium is accumulated in the kidney, especially in the proximal convoluted tubule, leading to kidney damage and chronic kidney disease [5][6][7][8]. Previous studies revealed that up to 7% of the global population suffers from chronic kidney disease caused by cadmium [9].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it becomes meaningful to intensify the research on elucidating the phytochemicals responsible for the aforementioned effects in order to maximize health benefits. High phytochemical content provides apple with its antioxidant properties and the consumption of apple juice is reported to have antigenotoxic potential [23]. Apple is rich in phloridzin that is mainly found in Malus species [24].…”
Section: Discussionmentioning
confidence: 99%
“…Сок из яблок обладает противовоспалительным эффектом, в частности, помогает снизить воспаление почек и мочевого пузыря, ускоряет процессы регенерации тканей, защищает от токсинов. [19]…”
Section: уменьшает воспалительные процессы в мочевыделительной системеunclassified